2020
DOI: 10.1001/jamanetworkopen.2019.19403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Mobile Monitoring System vs Usual Care on Depression Symptoms and Psychological Health

Abstract: Analyzed 1 Lost to follow-up 26 Analyzed 1 Lost to follow-up 33 Allocated to usual care 28 Received allocated intervention 7 Did not receive allocated intervention 7 Enrolled in study for <150 d when study ended 27 Received allocated intervention 6 Did not receive allocated intervention 6 Enrolled in study for <150 d when study ended Open Access. This is an open access article distributed under the terms of the CC-BY-NC-ND License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Five studies were identified in the area of early detection (Multimedia Appendix 1). Two of the studies were conducted in Germany [9,10], 2 in the United States [11,12], and 1 in Romania [13]. Two studies were financed by the EU [9,10], and 3 were funded by countries [11][12][13].…”
Section: Data Description: Prevention/early Detectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies were identified in the area of early detection (Multimedia Appendix 1). Two of the studies were conducted in Germany [9,10], 2 in the United States [11,12], and 1 in Romania [13]. Two studies were financed by the EU [9,10], and 3 were funded by countries [11][12][13].…”
Section: Data Description: Prevention/early Detectionmentioning
confidence: 99%
“…Optionally, the participants could also choose to receive motivational text messages regularly to ensure continuity. In Place et al [11], the intervention consisted of a monitoring system that collected different types of metadata and clinicians providing feedback. In Buntrock et al [9], the CG only received psychoeducation through the web-based platform.…”
Section: The Intervention Geton Mood Enhancermentioning
confidence: 99%
See 2 more Smart Citations
“…Many governments and philanthropic organizations have invested in the high‐risk research needed to explore the conditions through which fortifications in communication systems can improve health outcomes. Meta‐analyses of individually funded interventions have demonstrated that a strategic use of communication technology can: (a) reduce costs associated with in‐person visits (Chen et al, 2009); (b) can improve efficiencies and effectiveness of care (Buntin et al, 2011); (c) can improve outcomes through remote patient monitoring (Lee et al, 2018; Peterson et al, 2013); (d) can improve screening for early signs of mental distress (Place et al, 2020); and (e) can boost adherence to preventive measures equitably across populations (Wu et al, 2019). Typically, however, these benefits are demonstrated within a narrow sphere of application (Adler‐Milstein et al, 2014).…”
Section: A Global Priority To Strengthen Communication Systemsmentioning
confidence: 99%